6-Desaturase-Like Encoding Gene Introduction in Catfish (Clarias gariepinus) - Anny Hary Ayu; Alimuddin Alimuddin; Dedi Jusadi (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
African catfish (Clarias gariepinus) is one of the economically valuable aquaculture fish species in Indonesia. This research was aimed to produce F0 transgenic catfish carrying masou salmon Δ6-desaturase-like (OmΔ6FAD) gene. The Δ6-desaturase enzyme is involved in highly unsaturated fatty acid biosynthesis. Transgenic catfish was produced by sperm-mediated gene transfer using electroporation method. In this study, as the first step, sperms were electroporated with three different OmΔ6FAD concentration (25, 50, and 100 µg mL-1) to have the highest sperm viability after electroporation (125 V/cm, pulse frequency 5 times, pulse length 30 millisecond, pulse interval 0.1 second). The highest sperm viability and sperm carrying OmΔ6FAD were obtain at 100 µg mL-1. This concentration was then used to produce F0 transgenic catfish in the second step. Sperm motility, sperm viability, fertilization rate, hatching rate, and larval survival at 14 days after hatching were the same as the controls (p>0.05). Genomic DNA was extracted from caudal fin and then used as template to identify transgenic F0 by PCR method using specific primer for OmΔ6FAD gene. The PCR result showed that 53.84% of F0 carried OmΔ6FAD gene. The result of fatty acid analysis showed that EPA and DHA contents of F0 transgenic fish and non-transgenic fish were similar. Keywords: catfish, Δ6-desaturase-like gene, fatty acids, electroporation